Stanniocalcin-1 Expression in Normal Human Endometrium and Dysregulation in Endometriosis - Lusine, Aghajanova (Fertil Steril, 2016)
OBJECTIVE: To determine expression of stanniocalcin-1 (STC1) in human endometrium with and without endometriosis and its regulation by steroid hormones. DESIGN: Laboratory study. SETTING: University. PATIENTS: 19 women with endometriosis and 33 control women. INTERVENTION(S): Endometrial biopsy and fluid sampling MAIN OUTCOME MEASURE(S): Analysis of early secretory (ESE) and mid-secretory (MSE) endometrial secretomes from fertile women with nano-LC/MS/MS; real-time Q-PCR and immunohistochemistry for STC1 and its receptor CASR mRNA and proteins in endometrium with and without endometriosis; evaluation of STC1 and CASR mRNA expression in endometrial stromal fibroblasts (eSF) from women with and without endometriosis decidualized with E(2)P(4) or 8-bromo-cAMP. RESULTS: STC1 protein was strongly upregulated (p=0.0004) in MSE versus ESE in endometrial fluid of fertile women. STC1 mRNA significantly increased in MSE from women with, but not without endometriosis, compared to proliferative endometrium (PE) or ESE, with no significant difference throughout the menstrual cycle between groups. STC1 mRNA in eSF from control women increased >230-fold upon decidualization with cAMP versus 45-fold from women with endometriosis, which was not seen upon decidualization with E(2)/P(4). CASR mRNA did not exhibit significant differences in any condition, and was not expressed in isolated eSF. STC1 protein immunoexpression in eSF was significantly lower in women with endometriosis compared to controls. CONCLUSIONS: STC1 protein is significantly upregulated in MSE endometrial fluid, and is dysregulated in eutopic endometrial tissue from women with endometriosis. It is likely regulated by cAMP and may be involved in the pathogenesis of decidualization defects.